Molecular Assessment of Domain I of Apical Membrane Antigen I Gene in Plasmodium falciparum: Implications in Plasmodium Invasion, Taxonomy, Vaccine Development, and Drug Discovery - Che Roland Achungu; Damian Nota Anong; Robert Adamu Shey; Cevie Jesenta Tabe (Canadian Journal of Infectious Diseases and Medical Microbiology)
Given its global morbidity and mortality rates, malaria continues to be a major public health concern. Despite significant progress in the fight against malaria, efforts to control and eradicate the disease globally are in jeopardy due to lack of a universal vaccine. The conserved short peptide sequences found in Domain I of Plasmodium falciparum apical membrane antigen 1 (PfAMA1), which are exposed on the parasite cell surface and in charge of Plasmodium falciparum invasion of host cells, make PfAMA1 a promising vaccine candidate antigen. The precise amino acids that make up these conserved short peptides are still unknown, and it is still difficult to pinpoint the molecular processes by which PfAMA1 interacts with the human host cell during invasion. The creation of a universal malaria vaccine based on the AMA1 antigen is challenging due to these knowledge limitations. This study used genome mining techniques to look for these particular short peptides in PfAMA1. Thirty individuals with Plasmodium falciparum malaria had blood samples taken using Whatman’s filter papers. DNA from the parasite was taken out using the Chelex technique. Domain I of the Plasmodium falciparum AMA1 gene was amplified using nested polymerase chain reactions, and the amplified products were removed, purified, and sequenced. The DNA sequence generated was converted into the matching amino acid sequence using bioinformatic techniques. These amino acid sequences were utilized to search for antigenic epitopes, therapeutic targets, and conserved short peptides in Domain I of PfAMA1. The results of this investigation shed important light on the molecular mechanisms behind Plasmodium invasion of host cells, a potential PfAMA1 vaccine antigen sequence, and prospective malaria treatment options in the future. Our work offers fresh information on malaria medication and vaccine research that has not been previously discussed.